فاعلية االتعلم من الأقران في تحسين التحصيل الدراسي والدافعية لتعلم مادة العلوم لدى تلاميذ الصف التاسع بدولة الكويت - كندري، إبراهيم عبد الله محمد (Kulliyah of Education, International Islamic University Malaysia, 2020)
This research aims for exploring the effectiveness of the Peer Instruction approach in improving academic achievement and motivation among the ninth-grade science students in the State of Kuwait; and how this approach may increase the educational outcomes and influence the selection of learning methods following the educational environment. To achieve these objectives, the researcher used a quasi-experimental approach and applied it to a sample of 42 students who were randomly selected and divided equally into experimental and control groups. The experimental group underwent the program based on Peer Instruction, while the control group studied by the traditional method of the public schools in the State of Kuwait. Pre-test measurement for both groups was taken to assure that the groups are equal in terms of achievement in science. The researcher used the past year students' grades for the science subject. After completing the experiment, the researcher tested students' achievement and motivation toward learning science. Among the most important results is that there are statistically significant differences between the average scores of the experimental group, who studied with Peer Instruction, and the average scores of the control group, who studied traditionally, in both achievement and motivation to learn, where the experimental group scored higher in both. Thus, this research presents a few recommendations, including the adoption of the Peer Instruction method for teaching in general, and particularly for science subjects in secondary education.